2018
DOI: 10.1016/j.arth.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Techniques Help Understand Wear Patterns in Retrieved Total Knee Arthroplasty

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Differences in thickness between medial and lateral compartments were investigated using a peer reviewed method, based on micro-Computed Tomography (micro-CT) [17].…”
Section: Linear Deformation In Polyethylene Tibial Inserts (Micro-ct)mentioning
confidence: 99%
“…Differences in thickness between medial and lateral compartments were investigated using a peer reviewed method, based on micro-Computed Tomography (micro-CT) [17].…”
Section: Linear Deformation In Polyethylene Tibial Inserts (Micro-ct)mentioning
confidence: 99%
“…The debate around which coronal alignment is best after TKA is not yet resolved. Initially, there was a consensus on the need to restore the neutral femorotibial axis [7], to balance the stresses on both tibiofemoral compartments [2] and to decrease wear of the polyethylene insert, considered to be the weak point of arthroplasty system [3]. This resulted in increasingly sophisticated surgical techniques being used to improve the reproducibility of TKA implantation [1, 11, 13].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, several retrieval studies have demonstrated the correlation between implant position and deformation of the polyethylene tibial component [ 14 , 17 , 18 , 19 ]: varus alignments were associated with more deformed medial compartments, whereas valgus alignments were associated with more deformed lateral compartments. Our present study helps to join up these previous clinical and retrieval studies by demonstrating that the compartment with the more extended SPECT/CT signal showed the comparatively thinnest PE thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Retrieval analysis can help us further understand in-vivo implant performance and the influence of position and load distribution [ 14 ]. The association between increased bone tracer uptake in SPECT/CT, representing increased loading of the joint, and findings from retrieval studies have not, however, previously been investigated.…”
Section: Introductionmentioning
confidence: 99%